Snow Water Equivalent Modeling Capabilities of the GSSHA Watershed Model - Follum, Michael L; Downer, Charles W (2013)
This report demonstrates the snow water equivalent (SWE) modeling capabilities present within the Gridded Surface Sub-surface Hydrologic Analysis (GSSHA) model (Downer and Ogden 2004, 2006) by comparing simulated and observed snow accumulation data. GSSHA is used to simulate runoff, streamflow, and sediment and constituent transport in military and civil works projects. An energy balance method was originally used for calculating snow accumulation and melt, but now GSSHA has an optional temperature-index method and hybrid energy method. The full snowpack modeling capabilities of the Snowmelt Numerical-Analytical Package (SNAP) model (Albert and Krajeski 1998) have been included to simulate snowpack depth and density regardless of which snow accumulation model was used. With proficient SWE modeling capabilities, the GSSHA model can be utilized to solve complex watershed-related issues in regions where snow accumulation and melt are often the most critical source of water.